Trauma in the narratives of teachers during the pandemic: to process the experience of a political catastrophe (Simbiótica. Revista Eletrônica, 2025)
This study aimed to analyze narratives of memory and experience from female teachers regarding the Covid-19 pandemic period. To this end, ten public school teachers were interviewed. Traumatic effects of the pandemic context were observed, caused by the intensification of the exploitation of teaching work, stemming from the advance of neoliberalism, and by the resurgence of neoconservative attacks on teaching in its professional sense. The pandemic also catalyzed a privatization of the traumatic experience, given the individual accountability of teachers, which forced them to face its effects in isolation, in a context where workers’ social struggles and their class consciousness were already weakened. From an ethical perspective, listening to the teachers meant the possibility of establishing, together with them, meanings for their experiences, transforming them into a shared narrative and part of a set of individual stories with significant elements in common — like a story that is ours and should not be forgotten
Keywords: Pandemic; teaching work; trauma; neoliberalism